Scientific Literacy Skill Through Digital Media Professional Pdf Flip Based Book in Elementary School - Indira Bernica Krida Putri; Fitria Wulandari (Postgraduate, University of Mataram, 2022)
This study aims to determine the effect and how much of a professional flip pdf-based digital book media on science literacy skills in elementary schools. This research method uses descriptive quantitative research with the type of Pre-Experimental Design and the form of design used is one group pretest-posttest design. The instrument used in this study was a scientific literacy test sheet. The results showed that to test the hypothesis and answer the problem formulation, the data analysis techniques used were Eta squared and paired samples correlation. From the results of the Eta squared value, it was obtained at 0.850, which means that there is a big influence between professional flip pdf-based digital book media on scientific literacy skills, while if viewed from the paired samples correlation output above, it can be seen that the Sig (2-tailed) value is 0.000 which means more smaller than 0.05 means that there is a positive effect of professional flip pdf -based digital book media on the scientific literacy skills of elementary school students. The conclusion in this study is that the professional flip pdf-based digital book media has a positive and significant impact on the scientific literacy abilities of fourth grade students so that it can be used as a solution in elementary school learning.